2001
DOI: 10.1076/phbi.39.3.181.5932
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Phosphodiesterase Inhibitory Activity and Chemical Screening of Four Medicinal Plants

Abstract: Four medicinal plants, Acorus calamus Linn., Alpinia galanga Willd., Desmodium triquetrum D.C. and Vitis discolour Dalz., were investigated for potential to inhibit cyclic AMP phosphodiesterase. The alcohol extract of Desmodium triquetrum was found to be most active. The chloroform and alcohol extracts of Desmodium triquetrum and Acorus calamus, and the petroleum ether and chloroform extracts of Alpinia galanga contain flavonoids. These are possibly the active principles responsible for their anti-bacterial ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However extracts/bio-active compounds of theses plant (Alpinia galanga, Scutellaria baicalensis, and Forsythia suspensaand vitis vinifera) have been reported to produce neuroprotection against oxidant and inflammatory studies. Although, published data shows these plants are neuroprotective and have PDE inhibitory potential by restore cyclic nucleotide levelsin brain (Chit et al, 2001;Dell'Agli et al, 2005;Nikaido et al, 1989). Further mechanistic studies are required to investigate such types of mechanism.…”
Section: Plants Beneficial In Oxidative Stress/neuroinflammationmentioning
confidence: 89%
See 3 more Smart Citations
“…However extracts/bio-active compounds of theses plant (Alpinia galanga, Scutellaria baicalensis, and Forsythia suspensaand vitis vinifera) have been reported to produce neuroprotection against oxidant and inflammatory studies. Although, published data shows these plants are neuroprotective and have PDE inhibitory potential by restore cyclic nucleotide levelsin brain (Chit et al, 2001;Dell'Agli et al, 2005;Nikaido et al, 1989). Further mechanistic studies are required to investigate such types of mechanism.…”
Section: Plants Beneficial In Oxidative Stress/neuroinflammationmentioning
confidence: 89%
“…The extracts of plants (Ginko biloba, Poly tenuifolia and Acorus calamus) has also been reported to increase the ACh level in brain and found to be neuroprotective against AChE induced memory deficit. Although in other studies, these plants are reported for their PDE inhibitory potential (Chit et al, 2001;Macovschi et al, 1987;Nikaido et al, 1981) but further study is needed for identification of neuroprotective mechanism, by restoring cyclic nucleotide levels in relation to Alzheimer's disease.…”
Section: Plants Having Neuromodulatory Rolementioning
confidence: 95%
See 2 more Smart Citations
“…[ 7 ] It has been reported that alcohol extract of D. triquetrum was found to inhibit cAMP-PDE activity. [ 8 ] Therefore, the possible mechanism for significant anti-inflammatory activity of DTE may be by inhibition of cAMP-PDE activity and also it can be attributed to its antioxidant activity as evidenced by the presence of flavonoids. Further, the isolation of the compounds responsible for the claimed activities has to be taken up to support the present findings.…”
mentioning
confidence: 99%